Cell Wall Reinforcement in the Potato Tuber Periderm After Crop Treatment with Potassium Phosphite - Lobato, Maria Candela (2018)
The potato periderm is the outer tissue of potato tubers that protects the tuber from pathogen attack, dehydration, and wounding during harvest and storage. It is of secondary origin and replaces the epidermis early during tuber development. The outer layers of the periderm consist of cells with suberized walls. Phosphite compounds (Phi) are inorganic salts from phosphorous acid, and in previous works, we demonstrated that they are effective in protecting potato plants from biotic stress caused by different pathogens and also against UV-B radiation. The aim of the present work was to study the effect of Phi on the post-harvest potato periderm structure, cell wall components, and related enzymes. In three years of field experiments, potassium phosphite (KPhi) applications were compared with an untreated control. KPhi was applied to seed tubers before planting combined with foliage application of a conventional fungicide, to seed tubers and foliage without conventional fungicide, or to seed tubers combined with foliage application of KPhi plus a conventional fungicide. Observations of periderm sections showed increases in suberin and pectin depositions in post-harvest tubers from KPhi-treated plants compared to tubers from non-treated plants. In addition, peroxidase activity increased in the periderm tissue. The activity of laccases and superoxide dismutase was measured in the protein extract of the periderm, and an increase due to KPhi treatment was detected. The results presented here suggest that early KPhi treatment to seed tubers followed by foliage treatment leads to reinforcement of the cell wall of periderm cells, which represents a benefit for future response to stresses.